Analysis of Financial Statements for Assessing Performance at PT. Enseval Putera Megatrading Tbk. - Herliza Herliza; Oni Yulianti; Zahrah Indah Ferina (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the performance of PT. Enseval Putera Megatrading Tbk for the period 2015 to 2019. The data collection method uses the documentation method. The analytical method used is to use analysis of financial liquidity ratios, Solvability Ratio, Activity Ratio and Profitability Ratio. The research results prove that the performance at PT. Enseval Putera Megatrading Tbk, the liquidity ratio (Current Ratio, Quick Ratio, Cash Ratio) which has a good performance, namely, the Current Ratio with the calculation results from 2015-2019 has increased by 2.17 to 2.88 which means that the company is in a state of good because it reaches industry standard > than 2 times. Quick Ratio with the calculation results from 2015-2019 has increased by 1.39 to 1.92 which means that the company is in good condition because it has reached industry standards > than 1.5 times. While the cash ratio always increases and decreases, the cash ratio has a good performance only in 2016 and 2018, namely 52% because it is above the industry standard > than 50%. The solvency ratio (Debt Ratio, Debt To Equity Ratio) which has a good performance, namely, the Debt Ratio with the calculation results from 2015-2019 shows that the ratio value is getting better because it reaches the industry standard of 35%. The Debt To Equity Ratio with the results of calculations for 2015-2019 shows that the ratio value is good because it is below the industry standard < 90%. Total Asset Turnover and Fixed Asset Turnover) activity ratios show good performance, because both ratios reach industry standards, namely > 2 times and > 5 times. Profitability Ratios (Net Profit Margin, Roi, Roe). All the results of calculating the ratio for 2015-2019 did not increase at all because they were below industry standards.